Circumbinary and circumstellar discs around the eccentric binary IRAS 04158+2805 — a testbed for binary–disc interaction. Issue 1 (30th July 2021) - Ragusa, Enrico; Fasano, Daniele; Toci, Claudia; Duchêne, Gaspard; Cuello, Nicolás; Villenave, Marion; van der Plas, Gerrit; Lodato, Giuseppe; Ménard, François; Price, Daniel J; Pinte, Christophe; Stapelfeldt, Karl; et al.
ABSTRACT: IRAS 04158+2805 has long been thought to be a very low mass T-Tauri star (VLMS) surrounded by a nearly edge-on, extremely large disc. Recent observations revealed that this source hosts a binary surrounded by an extended circumbinary disc with a central dust cavity. In this paper, we combine ALMA multiwavelength observations of continuum and 12 CO line emission, with H α imaging and Keck astrometric measures of the binary to develop a coherent dynamical model of this system. The system features an azimuthal asymmetry detected at the western edge of the cavity in Band 7 observations and a wiggling outflow. Dust emission in ALMA Band 4 from the proximity of the individual stars suggests the presence of marginally resolved circumstellar discs. We estimate the binary orbital parameters from the measured arc of the orbit from Keck and ALMA astrometry. We further constrain these estimates using considerations from binary–disc interaction theory. We finally perform three SPH gas+dust simulations based on the theoretical constraints; we post-process the hydrodynamic output using radiative transfer Monte Carlo methods and directly compare the models with observations. Our results suggest that a highly eccentric e ∼ 0.5–0.7 equal mass binary, with a semimajor axis of ∼55 au, and small/moderate orbital plane versus circumbinary disc inclination θ ≲ 30° provides a good match with observations. A dust mass of 1.5× 10^-4 M_ best reproduces the flux in Band 7 continuum observations. Synthetic CO line emission maps qualitatively capture both the emission from the central region and the non-Keplerian nature of the gas motion in the binary proximity.